1995
DOI: 10.1021/j100017a063
|View full text |Cite
|
Sign up to set email alerts
|

Conductometric Study of Triple Ion Formation by Hydrogen Bonding Forces from Trialkylammonium Halides in Benzonitrile at Various Temperatures

Abstract: Electric conductances of tributylammonium (n-Bu3NH') or diethylcyclohexylammonium (EtzN(C6HII)H+) halides (chloride, bromide, and iodide) were measured in benzonitrile at 15, 25, 35, and 45 OC. Observed molar conductivities (NS cm2 mol-') for (0.4-6.0) x mol dm-3 of the salts were analyzed by our method. The ion pair and the "symmetrical" triple ion formation constants of the trialkylammonium chlorides (R3NHC1) decreased (instead of decreasing permittivity) with increasing temperature. Constant values of Walde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The difference in the polarized potential window of about 30 mV corresponds to a difference of about 3 kJ mol -1 in ion pairing of C 14 Iq + with Brand that with Cl -. The difference has been estimated to be about 6-9 kJ mol -1 for trialkylammonium ions 5 and about 1 kJ mol -1 for imidazolium ions, 36 which are comparable to the present estimate.…”
Section: Ionsupporting
confidence: 88%
See 1 more Smart Citation
“…The difference in the polarized potential window of about 30 mV corresponds to a difference of about 3 kJ mol -1 in ion pairing of C 14 Iq + with Brand that with Cl -. The difference has been estimated to be about 6-9 kJ mol -1 for trialkylammonium ions 5 and about 1 kJ mol -1 for imidazolium ions, 36 which are comparable to the present estimate.…”
Section: Ionsupporting
confidence: 88%
“…It is known that in organic solvents and also in aqueous solutions, the interaction between asymmetric tetraalkylammonium ions, such as methyltridodecylammonium with anions such as Cl - and Br - , is stronger than that between symmetrical quaternary ammonium and anions. Significant ion pairing is also known to occur between heterocyclic ammonium ions and Cl - or Br - . We can therefore expect stronger ion pairing when the cation constituting an RTIL is asymmetric (e.g., tetraalkylammonium ions having different alkyl chain lengths and heterocyclic ammonium ions at the RTIL|W interface). In fact, 1-methyl-3-octylimidazolium (C 8 mim + ) specifically adsorbs at the interface between 1-methyl-3-octylimidazolium bis(pentafluoroethylsulfonyl)imide ([C 8 mim + ][C 2 C 2 N - ]) and an aqueous solution of LiCl .…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated [8][9][10][11][12][13][14][15][16][17] by means of spectrophotometry, polarography, and conductometry that the "minor" complexation ability of lithium and sodium ions can be definitely observed if very low solvation media are employed. The presence of "reverse-coordinated" species, (M + ) 2 X -, and "coordinated" species, M + (X -) 2 , in nonaqueous solution has been discovered; where X -) RCO 2 -, [8][9][10] Cl -, 11 SCN -, 12 picrate ion, 13 , and (PhO) 2 PO 2 -, 14 and M + ) Li + and Na + for RCO 2 -, and Li + for other anions.…”
Section: Introductionmentioning
confidence: 99%
“…15 The temperature dependency of the formation constants of aggregates from R 3 NH + X -(X -) Cl -, Br -, and I -) in benzonitrile strongly suggested that the ion associations were governed mainly by hydrogen-bonding forces and not merely by Coulombic interactions. 17 The specific salt effects on acid-base reactions in nonaqueous solvents have been quantitatively explained by the "complex" formation 16,18,19 and not merely the ion exchange or the exchange between the contact ion pair (CIP) 20 and the solvent-separated ion pair (SSIP). 20 Thus, the cause was elucidated of a large variation in the indicator acidity (the Hammett acidity function) with the addition of various "indifferent" salts in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…On the other way, the influence of the dielectric constant on conductance of ionic liquids is satisfactorily accounted for by the inter ionic attraction theory in solvents of high dielectric constant, it is not completely known to what extent inter ionic forces are primarily concerned in solvents of low dielectric constant. There are some papers in low dielectric constant solvents [2][3][4][5]. Therefore, recently we have investigated the behavior of the ionic liquid in low dielectric constant solvents.…”
Section: Introductionmentioning
confidence: 99%